Accounting Information and Market Value of Quoted Manufacturing Firms: Panel Data Evidence from Nigeria - Innocent, Okoro; Ibanichuka, E.A.L.; Micah, L.C. (American Finance & Banking Review, 2020)
This study the relationship between accounting information and the market value of quoted firms in Nigeria. The general objective was to examine if accounting information have any effect on market value of quoted firms. Cross sectional data was sourced from financial statement of 23 manufacturing firm from 2008-2017. Market value of the firms was modeled as a function of earnings per share, return on equity and dividend per share. Ordinary least square method of cointgration, unit root and granger causality test was used to determine the extent to which human resource cost affect quality of financial report. After cross examination of the validity of the pooled effect, fixed effect and the random effect, the study accepts the fixed effect model. The study found that the independent variables explained 79 percent variation on the market value of the quoted firms. The beta coefficient of the variables indicates return on equity; earnings per share, dividend per share have positive effect on the market value of the quoted firms. From the regression summary, the study concludes that there is significant relationship between accounting information and market value of the quoted firms. The study recommends that management of the firms should formulate dividend policy that enhances the market value of the firms. Corporate strategies should be directed toward internal and external factors that affect earnings per share.